Off-grid PV system with batteries and hydrogen storage - Design and feasibility for a multifamily building in Sweden - Börling, Max (My University, 2018)
The Swedish electricity system relies mainly on nuclear and hydro power which together constitute approximately 80 % of the annual electricity production, but the deployment of new, renewable technologies is increasing. This increase has initiated a development from a centralized system to a more distributed system where several small actors both supply and consume electricity to or from the grid. One such technology is solar photovoltaics (PV), which has experienced a rapid growth during recent years. Due to the intermittent production characteristics of solar PV, the demand for energy storage solutions such as batteries are on the up-rise as well. This report evaluates how solar PV can be used in combination with a battery, a hydrogen storage (including an electrolyser and a fuel cell) and a heat pump to supply the annual heat and electricity demand of a building, without being connected to the grid. The building is assumed to be located in Gothenburg, Sweden and its energy demand is estimated based on the requirements from the Swedish passive house standard. The size of the components is determined and a functioning system configuration is found by modeling the system on an hourly basis. Furthermore, the cost of all components is estimated in order to evaluate the feasibility of the off-grid system also from an economic perspective. The results show that a PV system of 164 kWp, a battery of 300 kWh, a 66 kW electrolyser, a 20 kW fuel cell and a 25 kW heat pump is required to meet the annual demand of the building in off-grid mode. The results indicate that from a technical perspective, the mentioned technologies provide a feasible solution. However, from an economic perspective it is not viable with the current component costs. The results from the economic calculations show that the levelized cost of electricity (LCOE) ends up between 0,5 e/kWh and 1,43 e/kWh (1 e is approximately 10 SEK) depending on what assumptions are made. On the other hand, many of the technologies are still developing and not yet well-established on the market, which could mean that an energy system of this type can be an attractive alternative in the future.
Keywords: Samhällsbyggnadsteknik; Hållbar utveckling; Annan samhällsbyggnadsteknik; Energi; Innovation och entreprenörskap (nyttiggörande); Civil Engineering; Sustainable Development; Other Civil Engineering; Energy; Innovation & Entrepreneurship